Efeitos da mitomicina-c tópica em queimadura de camundongos - Rocha, Jose Lima de Carvalho (2010)
Many research works which are currently being carried out are driven towards the analysis of the mediators of the local and systematical immune inflammatory response after episodes of thermal aggression. Mitomycin-C (MMC), an insulated antibiotic of the Streptomyces caespitosus kind is used clinically in order to shorten the wound healing process due to its anti-proliferation action in fibroblasts in vitro. Dermal burns were produced on forty eight Swiss albine mice as a result of using an adapted iron-welding device which inflicted burns upon the back dorsum of the cavies for a lapse of time of nine seconds. On the first day the burns received topical treatment in a single dose with 0.9% sterile isotonic saline (control) or Mitomycin-C (MMC). The effects of MMC in the healing process of the burns were evaluated by using macroscopic, microscopic and computerized methods on the 4th day (PBD 4), 7th (PBD 7), 14th (PBD 14) and on the 21st post-burn day (PBD 21). For the macroscopic analysis an analogical visual scale (AVS) and a digital planimetry were used. On the microscopic analysis, the samples of the skin were colored by picrosirius red (PR) and analyzed at a microscope under a polarized light and the quantification of the collagen type I and III was carried out. The biometric parameters did not evidence any harmful effects over the nutritional conditions of the animals. The AVS evidenced that the wounds of the MMC group presented a significant better look than those of the control group in the PBD 14 (p= 0.0002). The wound edge migration rates (WEMR) evidenced a smaller rate in the MMC group than those of the control group, with significant difference (p =0.0033). The morphometry of the image processing, computer-assisted showed that the collagen type I presented a decreasing behavior in the process of healing in the control group, whereas in the group which was treated with MMC there was growth between PBD 4 and PBD 14 and a decrease between PBD 14 and PBD 21.Likewise, there was a significant difference among the groups on PBD 14 and a quite significant difference on PBD 21 in the amount of collagen type III on the wounds of the MMC, which evidences the capacity of MMC in slowing down the transformation of the immature collagen (type III) into a mature one (type I). MMC has proved to be efficacious in slowing the maturation of the wounds caused by thermal burns, thus generating a minor amount of fibrosis.